Persepsi guru terhadap pembelajaran dan pengajaran pendidikan muzik di sekolah - FARID KAMIL, AMELDA NATHRAH (2011)

(untitled)
This study aims to examine the extent to which teachers' views and perceptions of teaching and learning of music education in schools. This study is a study of the search effectiveness and benefits of learning and teaching music education in schools. Interviews methods and document analysis have been used to obtain and verify information from the study respondent. Method used in this study is qualitative in nature where the study is obtained through an interview conducted on 4 of the respondent’s teachers in two different schools. The result was transcipted interviews and qualitative analysis by questions research. The results study finds that all respondents consider the subject of music was important and needed in schools and the state through the learning and teaching music education to give an impression and impact on students in school.